The Role of Stress in Inflammatory Bowel Diseases - Sgambato, Dolores; Miranda, Agnese; Ranaldo, Rocco; Federico, Alessandro; Romano, Marco (Current Pharmaceutical Design, 2017)
Background: Inflammatory bowel disease (IBD) is a multi-factorial systemic disorder which involves immune, genetic and environmental factors. Stress, in its various forms, plays an important role in gastrointestinal diseases and, in particular, in IBD. Methods: Here, we focus on the environmental stressors in different aspects of IBD (pathogenesis, course and severity of disease) and, in particular, will evaluate the mechanisms by which they may influence IBD. Results: The effect of stress on IBD might be mediated by autonomic nervous system and hypothalamic pituitary adrenal axis. These nervous pathways are part of the so called “brain-gut axis” which links gastrointestinal integrity and functions to central nervous system acting through the increase of intestinal permeability, bacterial translocation and cytokines network. Conclusion: The incidence of emotional disorders is higher in Crohn's Disease and Ulcerative Colitis compared to general population. Moreover, depression and anxiety influence the course and the severity of the underlying intestinal disease. Hence, it is important to consider appropriate psychological therapy in IBD patients.
Keywords: inflammatory bowel disease